Application and Research of Information Technology in Art Teaching - Wang, Haiyin (Big Data Analytics for Cyber-Physical System in Smart City, 2021)
Information technology is the general trend of economic and social development in the world. The integration of information technology and other disciplines has become a new bright spot of school education and teaching reform in the 21st century in China. The design and development of the network learning system have become a hot field of education research, And the “student-centered” adaptive learning system is gradually replacing the “teacher (system) centered” network learning system. Information technology provides a lot of information and various means for art teaching and provides us with deeper and broader potential for the teaching content, teaching methods, and learning methods of art. Therefore, art teachers must combine advanced education ideas and methods with information technology to better achieve the basic purpose of art teaching. In the process of art learning, they use audio, light, electricity, and other visual presentation to stimulate and attract the attention of students and stimulate the students to learn art. Finally, the user model ontology is established, and the user model is improved by data mining technology.